Jarak Tanam Berbeda pada Uji Daya Hasil Lima Varietas Jagung Hibrida - Putri Dewangga Maharani; Ahmad Yunus; Dwi Harjoko (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2018)
Maize (Zea mays L.) is the second most important cereal crop of Indonesia after rice. The productivity of corn in Central Java province in 2015 was increased that considered as relatively low. Maize productivitiy needs to be improved to supply the requirement of people through of plant spacing and use the hybrid maize varieties. The aims of study was to determine the effectiveness level of plant spacing, to test the best hybrid maize varieties, and test the combination of two treatments to optimize the yield potential hybrid maize. This study has been conducted from June until October 2017, at Desa Srimartani, Kecamatan Piyungan, Kabupaten Bantul, Daerah Istimewa Yogyakarta. This study was arranged in Split Plot Design consisting of two factors that have been researched, varieties (ABCD, EFGH, NK6172, P27 and DK77) and plant spacing (70 x 20 cm, 75 x 20 cm, and 75 x 25 cm). The results show that treatment of varieties mostly can increase all of variable analysis but there is no interaction on both treatment except plant height, fresh and dry biomass weight. Variable of plant height, tasseling and silking, cob weight with husk, cob weight without husk, kernel seeds weight per plot, 100 seeds weight, yields per hectare show that the highest average is variety of P27. While treatment of plant spacing has no effect because the interval between treatments plant spacing is too close therefore it shows insignificantly different result. The highest dry kernel product on variety treatment P27 (8,82 ton ha-1), followed by DK77 (8,53 ton ha-1), ABCD (8,50 ton ha1), NK6172 (8,34 ton ha-1), and EFGH (7,13 ton ha-1).